2001
DOI: 10.1179/026708401101517593
|View full text |Cite
|
Sign up to set email alerts
|

Gas nitriding – process control and nitriding non-ferrous alloys

Abstract: This paper, based on the Second Lakhtin Memorial Lecture, gives an overview of the developments in the process control of gas nitriding and describes the current status of nitriding of non-ferrous alloys. Control of the nitriding process involves both thermodynamic and kinetic factors. On this basis, Lakhtin developed concepts that provide the foundations for controlled gas nitriding processes. The progress in the development of sensors in the last few years offers new possibilities for gas nitriding and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Other studies showing the effectiveness of similar solutions were recently reported [26]. The beneficial effect of magnesium as an alloying element in an aluminum substrate on the kinetics of nitriding under glow discharge conditions was also earlier described [5,9]. However, an unfavorable phenomenon accompanying glow discharge nitriding related to the formation of a high near-surface concentration of magnesium in the form of zones of magnesium, MgO, which negatively impacts the effects of nitriding machine parts in industrial practice, was also reported [27].…”
Section: Aluminum Nitriding-state Of the Artmentioning
confidence: 61%
See 2 more Smart Citations
“…Other studies showing the effectiveness of similar solutions were recently reported [26]. The beneficial effect of magnesium as an alloying element in an aluminum substrate on the kinetics of nitriding under glow discharge conditions was also earlier described [5,9]. However, an unfavorable phenomenon accompanying glow discharge nitriding related to the formation of a high near-surface concentration of magnesium in the form of zones of magnesium, MgO, which negatively impacts the effects of nitriding machine parts in industrial practice, was also reported [27].…”
Section: Aluminum Nitriding-state Of the Artmentioning
confidence: 61%
“…Early research carried out in the field of plasma-assisted nitriding of aluminum alloys [3] confirmed that nitriding under glow discharge conditions, in particular the phenomenon of cathodic sputtering, creates favorable conditions for the growth of surface layers of aluminum nitride of the AlN type with thickness up to a few µm. It was shown that even in medium vacuum conditions (10 −2 -1 Pa), a typical industrial facility for plasma nitriding steel can be successfully used to carry out the processes [5]. At the same time, the beneficial effect of the AlN layer on tribological resistance was confirmed [3].…”
Section: Aluminum Nitriding-state Of the Artmentioning
confidence: 97%
See 1 more Smart Citation
“…Underneath the compound layer, a socalled diffusion zone develops in the ferrite matrix, in which nitrogen is interstitially dissolved. The compound layer can improve the wear and corrosion resistance significantly, whereas the diffusion zone can enhance the fatigue strength [5][6][7][8]. Rapid quenching is not required after the conventional gas nitriding treatment; thus, it prevents dimensional distortion [9].…”
Section: Introductionmentioning
confidence: 99%